The Importance Of Sex In Marriage Reflected In D.H. Lawrence's Lady Chatterley's Lover Novel (1928): A Psychoanalytic Perspective - Puspitasari., Ratih, Dr. M. Thoyibi, M.S, Titis Setyabudi, S.S., M.Hum (2013)
This study is about the importance of sex in marriage in Lady Chatterley's Lover. The objectives of the study are conducted to identify the indicators of the need for sex of the major character, to describe the major character attempt to meet the need, and to reveal the underlying reason of why the major character did viewed from the psychoanalytic perspective. The object of the study is Lady Chatterley's Lover by D.H. Lawrence. It used psychoanalytic perspective. This research is a descriptive qualitative research. The type of data in this study is a text that consists of words, phrases and sentences. There are two data sources in this study. The primary data source is Lady Chatterley's Lover by D.H. Lawrence. The secondary data source consists of the other data, which have a relationship with the study, such as some biography of the author, and other relevant information. The result of the study shows the following conclusions. First, based on the structural analysis the author wants to deliver a message that the meeting of sexual need is important in marriage. Second, based on the psychoanalytic perspective, it clear that in this novel D.H. Lawrence describes psychological phenomena in which one is seeking for the sexual satisfaction from a person other than one‟s spouse.